Folk Taxonomy of Poaceae in Mongolia - Yu. Konagaya; K. Suzuki; A. Hotta (Nomadic Civilization: Historical Research, 2024)
This article is the English translation of Japanese original text “Mongol ni okeru Ineka no Minzoku bunrui” written by Yuki Konagaya and others published in 2024 in “Japan and Mongolia” (58: 139-157). In this article, the authors clarified the naming characteristics of Poaceae by comparing the Mongolian names and the academic names. While scientific names are hierarchical and do not overlap, folk names can be classified and named by ears or tip, awns, roots, at the same time, therefore multiple plant names can be used as one species.